Implementation of Regional Financial Administration Management Labuhan Batu Utara Regency by System Decentralization (Study in the Office of BPKAD Labuhan Batu Utara Regency) - Ananda, Sobri (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2023)
Regional autonomy is the essence of decentralized governance. So far, decentralization has been implemented and has been running effectively. Not only that, decentralization also affects people's behavior which previously only focused on the center of power. In terms of regulating regional finances, analyzing regional taxes and levies, it turns out that the ratio of the increase in regional revenues from regional levies since regional autonomy has been higher than the ratio of the increase in regional revenues from regional taxes, especially in urban districts. One of the districts studied in this study is North Labuhan Batu Regency. This study aims to determine the implementation of local government accountability for the management of regional financial administration, the implementation of a regional decentralization system in the management of regional financial administration in North Labuhan Batu Regency, as well as obstacles or obstacles in the management of regional financial administration in North Labuhan Batu Regency. This research method uses this type of research and the approach uses empirical juridical research, with data sourced from Islamic law, primary and secondary data obtained through interviews and literature studies. Then, the data was processed using qualitative analysis. Based on the results of the study, it is known that the implementation of local government accountability for the management of regional financial administration includes the process of managing, administering, providing and using money in every cooperative effort of a group of people to achieve a goal. The implementation of a regional decentralization system in the management of regional financial administration in North Labuhanbatu Regency is realized by the government forming an agency called the Regional Financial and Asset Management Agency (BPKAD). BPKAD helps achieve priority programs to encourage the achievement of the Vision and Mission that has been set by the North Labuhanbatu Regency Government. Constraints or obstacles, including the very fast changes in laws and regulations without being followed by socialization, the limited understanding of the apparatus on the technical aspects of budget preparation and allocation of funds, especially in determining spending priorities, with reference to the principle of performance-based budgeting, and the need for continuous structuring. relating to the administrative system, the mechanism of regional taxation/levies procedures that have accommodated various new regulations that apply.